Electrocorrosion and protection of metals - Riskin, Joseph; Khentov, Alexander (Elsevier, 2019)
Electrocorrosion and Protection of Metals, Second Edition, compiles theoretical and practical information, outlines the specific problem, and presents the available solutions related to corrosion by external currents. Basic data on the behavior of different metals under the attack of anodic, cathodic, direct and alternating currents is considered, as are the problems of electrocorrosion-from the identification of corrosion damage and detection of the external current sources, to the selection of optimal means and methods of mitigation, monitoring and protection of different metallic structures and structures of reinforced concrete. This book includes comprehensive information and provides necessary links to more detailed, original sources, thus enabling users to solve either general or particular problems of electrocorrosion and protection of metals.